Toxic effects of malathion in carp, Cyprinus carpio carpio: Protective role of lycopene - Yonar, Serpil Mise (Academic Press Inc Elsevier Science, 2013)
The present study was carried out in order to investigate the potential protective effects of lycopene against malathion-induced toxicity in carp. The fish were exposed to sublethal concentrations of malathion (0.5 and 1 mg L-1) for 14 days, and lycopene (10 mg kg(-1) of fish weight) was simultaneously administered. Samples of the blood and tissue (liver, kidneys, and gills) were collected at the end of the experimental period and their haematological profiles [red blood cell (RBC) counts, haemoglobin (Hb) concentrations, haematocrit (Ht) levels, and erythrocyte indices, including the mean corpuscular volume (MCV), the mean corpuscular haemoglobin (MCH) and the mean corpuscular haemoglobin concentration (MCHC)], immune responses [white blood cell (WBC) counts, oxidative radical production (nitroblue tetrazolium (NBT) activity), total plasma protein (TP) and total immunoglobulin (TI) levels and phagocytic activities (PA)] and oxidant/antioxidant statuses [malondialdehyde (MDA) levels, superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) activities, and reduced glutathione (GSH) concentrations] were analysed. The findings of the present study demonstrated that the exposure of carp to malathion resulted in alterations in the haematological profiles and immune responses, and lead to increased reactive oxygen species formation, resulting in oxidative damage and inhibition of the antioxidant capacities. However, the administration of lycopene prevented malathion-induced toxic effects. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Malathion; Lycopene; Haematology; Immunity; Oxidative stress; Carp